Patient-reported outcomes in a linguistically diverse cancer population: Addressing barriers to access. Issue 28 (1st October 2022) - Usman, Fatima; Rittberg, Rebekah; Lim, Howard John; Bhang, Eric; Chan, Brandon; Alex, Deepu; Chia, Stephen K.L.; Gill, Karamjit; Ko, Jenny J.; KoLeong, Jason; Laskin, Janessa J.; Loree, Jonathan M.; et al.
Abstract : 168 Background: The census metropolitan area served by BC Cancer is Vancouver which has a population of 2.4 million. Census Canada noted the mother tongue learned in childhood and still spoken was: 54% English, 17% Indo-European, 16% Chinese, 10% Indo-Iranian, 3% English+other language, 2% other. At BC Cancer, implementation of patient reported outcomes (PROs) was launched 1 year ago with consideration of preferred language. Our goal was to examine the implementation of PROs with respect to equity of access and language preferences. Methods: BC Cancer Vancouver implemented PROs including the Edmonton Symptom Assessment Scale Revised, Canadian Problem Checklist and EQ5D in April 2021 using a web-based platform. A 1-year cohort was reviewed for patients' mother tongue and the language used for the PROs. Qualitative interviews were undertaken for non-English mother tongue patients to ask for preferred language of PROs and reasons for the choice if mother tongue was not selected. Results: 86 patients were enrolled in the PRO program. Baseline characteristics: 66% female, age 30% < 60/ 31% 60-69/ 39% >70, primary site 54% lung/ 34% colorectal/ 18% other. Ethnic origin: 53% North American and European, 40% East and Southeast Asian, 2% Latin/Central and South American, 3% South Asian, 1% Indigenous, 1% other. Mother tongue: 52% English, 48% non-English (39% English proficient, 9% low English proficiency). Patient preferred language for PROs: 81% English, 11% Chinese, 7% other. Reasons for non-English mother tongue preference for English language included comfort with written English, use of family assistance completing questionnaires for both language and familiarity with electronic devices. Conclusions: In the Vancouver linguistically diverse cancer population, the majority of patients preferred English language PROs. Reasons for this include proficiency in the written language and the use of family members to complete the questionnaires. With 39% of patients over the age of 70 in our study, the use of electronic devices for completion may have introduced an additional barrier to access. In clinic iPad questionnaires with nursing and care aide support have been introduced to help address this gap. Clinical trial information: NCT05057234.